Implementasi problem-based learning berbasis education for sustainable development terhadap kemampuan berpikir kritis peserta didik - Veronica Christiani Gurning; Ganda Hijrah Selaras (Universitas Sebelas Maret, 2025)
ENLearning plays a crucial role in the educational process; therefore, educators need to apply learning models that can improve students' critical thinking skills. One of the most effective approaches is to use a Problem-Based Learning model centered on education for Sustainable Development, which aligns with 21st-century competencies. The Education for Sustainable Development approach is critical to understanding environmental changes from the perspective of developing students' character. This research aims to review the literature on the Problem-Based Learning model centered on Education for Sustainable Development in improving students' critical thinking capacities. The methodology was a literature review of 20 papers from the last five years found in scientific databases like Sinta and Scimago. There were five articles in the sampling. Based on the analysis, the ESD-based Problem-Based Learning model positively influences students' critical thinking skills.IDPembelajaran merupakan komponen penting dalam proses pendidikan, sehingga diperlukan model pembelajaran yang dapat meningkatkan kemampuan berpikir kritis peserta didik. Salah satu cara yang paling efektif adalah dengan menerapkan model pembelajaran Problem Based Learning berbasis Education for Sustainable Development yang sesuai dengan kompetensi di era abad 21. Pendekatan Education for Sustainable Development sangat penting untuk memahami perubahan lingkungan hidup dari sudut pandang pengembangan karakter peserta didik. Tujuan penelitian ini adalah untuk mengkaji literatur terkait model Problem Based Learning berbasis Education for Sustainable Development dalam membantu peserta didik untuk meningkatkan kemampuan berpikir kritis. Metode yang digunakan adalah studi literatur terhadap 20 artikel dari database ilmiah seperti Scimago dan jurnal yang terindeks Sinta dengan rentang 5 tahun terakhir. Sampel yang digunakan adalah 5 artikel. Berdasarkan hasil analisis, model Problem Based Learning berbasis ESD memiliki pengaruh positif terhadap kemampuan berpikir kritis peserta didik.